Mendelian randomization and transcriptome analysis reveal depression-driven regulatory patterns of the immune microenvironment in myocardial infarction and heart failure - Zhou, Zihao; Yu, Xiaotongning; Jin, Yani; Liu, Ziyi; Liang, Guoqiang; Ma, Ben; Hou, Anqi; Gu, Tongfei; Xu, Na; Sun, Shuo (Frontiers in Immunology, 2026)
BackgroundMajor depressive disorder (MDD) and cardiovascular diseases (CVD) are mutually amplifying global health burdens, yet the causal directions and immune-determined molecular substructures that link MDD to myocardial infarction (MI) and heart failure (HF) remain poorly resolved.MethodsBidirectional two-sample Mendelian randomization (MR) was applied to large-scale GWAS (1.35 million MDD; 361 K MI; 977 K HF) followed by replication in 11,004 NHANES 2005–2020 participants using restricted cubic splines and multivariable logistic regression. Multi-cohort transcriptomics (peripheral blood microarray n = 447; in-house RNA-seq n = 14; left-ventricular tissue from dilated cardiomyopathy (DCM) patients (n = 332) were integrated to identify MDD-driven expression signatures. LASSO regression, CIBERSORT, ssGSEA, consensus clustering and GSVA were employed to derive diagnostic gene panels and immune endotypes.ResultsMR analyses provided genetic evidence consistent with a directional effect of MDD on MI (IVW β = 0.01, P = 4.6 × 10⁻6) and HF (IVW β = 0.19, P = 1.3 × 10⁻6) without reverse causation. Depression (PHQ-9 ≥ 10) has a dose-dependent nonlinear association with MI and HF (P<0.0001), with adjusted odds ratios (OR) of 1.80 (95% CI: 1.07-3.05) and 2.41 (95% CI: 1.45-4.00), respectively. A total of 202 MDD-related genes were identified through integrated transcriptomic analysis. After cross validation with the MI/HF dataset, six robust biomarkers (TMEM43, C1orf174, L3MBTL4, OR52N4, SLC25A20, MISP3) were screened. Risk-score models discriminated MI (AUC = 0.90–1.00) and HF (AUC = 0.95) in peripheral blood, but HF discrimination in cardiac tissue was modest (AUC = 0.60). Consensus clustering on 184 MDD-correlated genes stratified each CVD into two reproducible subtypes: a “homeostatic/pro-fibrotic” cluster enriched for ribosomal and cell-cycle pathways and an “inflammatory-metabolic” cluster characterized by NF-κB, TNF-α, IL-6, complement and coagulation activation.ConclusionsGenetic, epidemiological, and multi-omic evidence supports a directional association between MDD and increased risk of MI and HF. We deliver reproducible blood-based gene panels and immune endotypes that dissect biologically distinct MDD-CVD substructures, offering actionable targets for precision immunomodulatory therapy in cardio-depressive comorbidity.